Investigations on density and surface roughness characteristics during selective laser sintering of Invar-36 alloy. (8th May 2019) - Khanna, Navneet; Mistry, S; Rahman Rashid, R A; Gupta, Munish Kumar
Abstract: Invar-36 is used in several applications ranging from aerospace parts to LNG tanks owing to its inherent properties such as low thermal expansion. However, in practice, most of the Invar-36 components are machined from bulky wrought workpieces, rendering it an expensive material. In this case, additive manufacturing of this alloy to a near-net shape would be very useful in promoting its usage. On the contrary, very limited literature is available that reports on the 3D printability of this alloy. Therefore, the main objective of this research was to comprehend the influence of various selective laser sintering (SLS) process parameters on density and surface roughness of the printed Invar-36 coupons followed by statistical analysis and optimization study. For this, a linear relationship has been made between the density/surface roughness and the energy density during the process. Further, the S/N ratio plots have been implemented for technical investigations of density and surface roughness i..e., from top and side face values. Finally, the optimization has been performed by using nature inspired algorithms i.e., Moth Flame Optimization and Dragonfly Algorithm Optimization. The overall results depicts that the least dense coupon consisted of partially bonded particles exhibiting first kind of balling phenomenon whereas the most dense coupon largely contained voids/pores, characteristic of the printing process.